Reviewing Translation Technique in Niki’s La La Lost You: A Case Study - Ekasaputri, Dessy; Afifulloh, M; Widyasari (Smart Edu Center, 2023)
Techniques for translating a song are very varied. This is because the native language (TL) can be culturally different from the target language (TL). Translation does not only shift the source language to the target language, but translation is also closely related to socio-cultural influences and the formation of cultural identity between the two languages. Based on Newmark’s (1988) theory, this research aims to find the translation method used by translator Cyntia Maharani in translating a song entitled La La Lost You by Indonesian singer Niki. the research results explain that the translator used the semantic translation, literal and free translation, and aesthetic consideration. All the techniques are more oriented towards the target language (TL).